2021
DOI: 10.3390/forecast3020021
|View full text |Cite
|
Sign up to set email alerts
|

Queue Length Forecasting in Complex Manufacturing Job Shops

Abstract: Currently, manufacturing is characterized by increasing complexity both on the technical and organizational levels. Thus, more complex and intelligent production control methods are developed in order to remain competitive and achieve operational excellence. Operations management described early on the influence among target metrics, such as queuing times, queue length, and production speed. However, accurate predictions of queue lengths have long been overlooked as a means to better understanding manufacturin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A technological system as a set of machines and production equipment with the flow of products and the probability of equipment failure (in case of failure) can serve as a mass service system. Scientists have developed a number of solutions to improve the efficiency of the production system: the method of identifying «bottlenecks» in the technological process in the conditions of Industry 4.0 [40], a model for the accurate forecasting of queue length [41], a model of a repairable mass service system [42], etc.…”
Section: Focus Of Mass Maintenance Models On Capital Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…A technological system as a set of machines and production equipment with the flow of products and the probability of equipment failure (in case of failure) can serve as a mass service system. Scientists have developed a number of solutions to improve the efficiency of the production system: the method of identifying «bottlenecks» in the technological process in the conditions of Industry 4.0 [40], a model for the accurate forecasting of queue length [41], a model of a repairable mass service system [42], etc.…”
Section: Focus Of Mass Maintenance Models On Capital Resourcesmentioning
confidence: 99%
“…Scientists see the solution to the problem of queue management as optimizing its length. So, May et al, in the example of semiconductor production using machine learning tools, offer the following heuristic approach [41]:…”
Section: Focus Of Mass Maintenance Models On Capital Resourcesmentioning
confidence: 99%
“…In recent decades, many researchers and practitioners have tried to predict stock prices using various methods, including time-series-based prediction methods [7,8], machine learningbased prediction methods [9,10], deep learning-based prediction methods [11][12][13][14], and so on. However, due to the characteristics of stock prices, such as non-linearity, high noise, and variability, it is often difficult to achieve the desired prediction results with these methods [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The ML approaches can reveal different complex patterns defined by nonlinearity and some relationships that have difficulty discovering linear algorithms. The approaches are widely used to predict cloud services [2], health [3], energy [4], and many other real-world problems.…”
mentioning
confidence: 99%
“…In the paper Queue Length Forecasting in Complex Manufacturing Job Shops by May et al [4], the authors introduced an approach to retrospectively identify queue lengths based on transitional data. The study found that accurate queue length prediction is feasible by applying various techniques, which can enable further research and predictions.…”
mentioning
confidence: 99%